Development of STEM-Based Educational Games As Differentiated Learning Media to Improve Students' Creative Thinking Skills - Hidayati, Siti Anisa; Hariyadi, Slamet; Putra, Pramudya Dwi Aristya (Jurnal Paedagogy, 2024)
This study aims to analyze the validity of developing STEM-based educational games on force and movement material to improve junior high school students' creative thinking skills. This research method used research and development with the ADDIE model involving three stages: analysis, design, and development, but each stage was always evaluated. The research subjects consisted of 32 students of SMPN 3 Jember class VII and two teachers. The research object was an analysis of the needs of teachers and students in developing STEM-based educational games. The data collection instrument was a validation sheet with data analysis techniques in the research, including validity test analysis techniques and questionnaires to determine needs analysis. The research results obtained were an analysis of teacher needs of 100% and an analysis of student needs of 80% to develop the quality of STEM-based educational game learning media. Data analysis of the average assessment score of the three expert validators was 93%, showing that the category was very valid so that STEM-based educational game development products can be used, but there are slight revisions.